Frequency Evaluation of T6235C (m1) and A4889G (m2) Polymorphisms of CYP1A1 Gene in a Healthy Population from the west of Mazandaran Province, Iran - Ahangar, N; Alizadeh, B; Tousi, A (Cellular and Molecular Biology, 2016)
CYP1A1 is an important phase I xenobiotic metabolizing enzyme involved in the metabolism of numbers of toxins, endogenous hormones and drugs. Polymorphisms in this phase I gene can alter enzyme activity and induction, also are known to be associated with cancer susceptibility related to environmental toxins and hormone exposure. The present study was aimed to determine the frequencies of commonly known functional polymorphismsof CYP1A1 gene including CYP1A1 m1 (MspI), and CYP1A1 m2 (Ile-Val) in a healthy population from the west of Mazandaran province, Iran. A total of 200 unrelated healthy subjects from Mazandaran province, residing in Tonekabon city, coming for blood donating at Tonekabon Blood Transfusion Center were enrolled. Genomic DNA was extracted from peripheral blood lymphocytes of each subject. All subjects were genotyped for CYP1A1 m1 (T>C) and m2 (A>G) by polymerase chain reaction-restriction fragment length polymorphism method. The frequencies of the TT(wt/wt), TC(wt/mt) and CC(mt/mt) genotypes were as 65.5%, 32.0% and 2.5% respectively for m1 and frequencies of the AA(wt/wt), AG(wt/mt) and GG(mt/mt) genotypes were as 84.5%, 15% and 0.5% respectively for the m2. The frequencies of T and C alleles in the population were 81.5% and 18.5% respectively and the frequencies of A and G alleles were 92% and 8% respectively. Results of the present study might be important in understanding the distribution of CYP1A1 (m1) and CYP1A1 (m2) polymorphisms in Mazandaran province of Iran. Moreover, these results may determine the susceptibilities of individuals towards environmental procarcinogens that result in several cancers.